До 200-річчя видатного ботаніка Е.-Р. Траутфеттера - Melnik, V.I.; Kudrenko, I.K. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
It is covered formation E.-R. Trautfetter as a known botanist and his contribution to development of systematization and other field of botany. Special attention is given to role of scientist in creation of Botanical garden at the Taras Shevchenko Kyiv National University.